Resveratrol regulates cytokine secretion by cardiac microvascular endothelium under hypoxia/reoxygenation condition. (14th October 2021) - Cui, H; Yang, Y J; Zong, W J
Abstract: Background: Microvascular endothelial injury is recently considered playing an initial role in myocardial ischemia/reperfusion injury (MIRI). Cardiac microvascular endothelial cells (CMECs) regulate cardiomyocytes and haematocytes via secreting cytokine. MIRI jeopardize not only the barrier function but also the paracrine function of microvasculature. Resveratrol, a natural polyphenolic compound, was demonstrated to protect myocardium against MIRI and to preserve the function of endothelium. However, how the paracrine function of CMECs is regulated by MIRI and resveratrol remains to be elucidated. Purpose: The study was to illuminate the alteration of cytokine profiles secreted by CMECs under hypoxia/reoxygenation (H/R) condition and its modulation by resveratrol. Methods: CMECs were exposed to different concentrations of resveratrol for 30 minutes and then were subjected to H/R for 12 h/2 h. Apoptotic rates were measured to determine the optimal concentration. Protein antibody arrays were performed to find the alteration of cytokine secreted into conditioned medium by CMECs. A Gene Ontology (GO) analysis was applied to interpret the functional implication of changes in cytokine profiles. Results: Resveratrol inhibited apoptosis of CMECs in a dose-dependent manner after H/R and reached its peak effect at the concentration of 100μM, which reduced apoptosis from 27.27±2.95% to 15.01±1.36% (Figure 1A and B). The results of a cluster analysis and all significantly altered factors are shown in figure 1C (fold-change >1.5; p<0.05). Twenty-nine types of cytokine were significantly changed by H/R (15 factors decreased and 14 increased, Figure 2A), and resveratrol at 100μM changed 98 types of cytokine compared with the H/R group (93 factors decreased and 5 increased, Figure 2B). Among these cytokine, eight factors were increased by H/R and they were decreased by resveratrol. Eleven were attenuated by H/R and further decreased by resveratrol. Insulin-like growth factor binding protein-1 was up-regulated by H/R and it was further increased by resveratrol (Figure 2C). The factors with significant alteration were involved in cellular growth, proliferation and differentiation, as well as chemotaxis and transport. Conclusions: Resveratrol inhibited the apoptosis of CMECs and modulated the paracrine function of cardiac microvascular endothelium under ischemia/reperfusion condition. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Natural Science Foundation